Theoretical determination of the law of motion of vibrating plate at surface compaction of polymer concrete - Maslov, Alexandr; Savielov, Dmitry; Vakulenko, Roman (Academic journal Industrial Machine Building Civil Engineering, 2021)
To theoretically determine the law of motion of a vibrating plate with polymer concrete, the dynamic system "vibration plate - polymer concrete" was researched. The compacted polymer concrete in it is presented as a system with distributed parameters, which takes into account the action of elastic and dissipative resistance forces from polymer concrete at its surface compaction. In accordance with the accepted rheological model of polymer concrete, a partial derivative ratio between stress and deformation is proposed for conditions of a uniaxial stress state. A vibration wave equation describing the motion of the compacted polymer concrete was created. Its solution enables the determination of the law of propagation of elastic-viscous deformation waves in polymer concrete.